Study on environment modeling and electromagnetic scattering characteristics in mountainous areas. Issue 3 (3rd April 2022) - Wang, Zhao Long; Tong, Chuang Ming; Wang, Yi Jin; Wang, Qing Kuan; Zou, Gao Xiang
ABSTRACT: This paper proposed a modeling method to describe the environmental structure of mountainous areas by using the composite rough surface model, and the electromagnetic (EM) scattering characteristics of the composite rough surfaces are studied. Based on the Monte Carlo method and Gaussian spectral function, the rough surface of the terrestrial environment is generated. And the inverse tangent function is introduced to weighted rough surfaces with different statistical properties, making rough surfaces join smoothly. On this basis, geometric models of rough surfaces of three typical mountainous environments, valley, hillside, and ridge, are established. The shooting and bouncing ray (SBR) method is used to calculate the EM scattering characteristics. Due to the multiple reflections of EM waves, the idea of ray-density normalization (RDN) is introduced to improve the EM flow on triangular facets illuminated by multiple rays. Finally, the effects of different slope angles, surface roughness, and incident wave angles on the EM scattering characteristics are discussed to provide some useful conclusions. The simulation results show that the rough surface with a certain slope will greatly change the scattering characteristics of the whole environment and make the spatial distribution of scattering energy show a new characteristic.